Carcinogenic effect of external formula on skin: a clinical study - Alabbody, Huda Hameed Kadhim (International Journal of Psychosocial Rehabilitation, 2020)
There are numerous risk factors for cancer occurrence, including: age, family history, microbial infections, lifestyle and contact with harmful exogenous or endogenous factors associated with touching, eating, drinking, or breathing. The aim of this study was to estimate the potential carcinogenic effect of using some cosmetics and household detergents by cancer patients and to describe their toxic and carcinogenic ability.Methods: One hundred of cancer patients from Baghdad city were included in the questionnaire during the period from June to September 2019, in which the frequency of using ten different items( external formulas) was investigated. which in contact with the skin.Results: The results indicated that the most vulnerable age for cancer among the individuals who used to deal with chemicals was the 50s (29%). While the highest rate of cancer was the breast cancer in women (22%), lung and tracheal cancer in men accounted for18% and gut cancers ranked third (14%) in both sexes. Housewives reported the highest number of cancer cases (30%), followed by the group of painters, carpenters, barber and building workers (20%), and finally the group of drivers and oil workers (15%). There was a significant value for the daily use of the selected items, especially powder detergents, liquid cleaning products, , skin moisturizes, and sunblock. However, no significant value appeared when cancer patient used these items weekly or monthly.Conclusion: The excessive use of chemicals can cause many health disorders, one of them is cancer. Therefore, it is recommended to use alternative and safe products instead of those containing chemicals as much as possible to avoid direct their effects, such as burns, allergies, or cancer at the long term.